Pengaruh Model Pembelajaran Tutor Sebaya terhadap prestasi belajar matematika siswa - Petrus Abineno; Yohana Rina Rowa; Yohanes Ovaritus Jagom (Asimtot : Jurnal Kependidikan Matematika, 2019)
This Main problem in this research that is about how execution of study model of tutor coeval on sub subjek of rectangular in SMP Negeri 20 Kupang city academic year 2017 / 2018. The purpose this research is to know implementation of learning and the effect of learning model tutor coeval to achievement learn mathematics student’s on sub subjek of rectangular in SMP Negeri 20 Kupang city academic year 2017 / 2018.This research was conducted on VII grade student’s SMP Negeri 20 Kupang city which amounted to 30 students selected randomly from 5 classes available.The instrument used in thes research are observation ,interview and achievement tes learn much as 30 problem item in from of double helix.Data analysis technique used in this research that is result of observation .result of interview,achievement of indicator and t-test. Based on the results of observation , result of interview,achievement of indicators,obtained achievement learn mathematics student are very good. While based on t-test calculation shows t count= 16,417 and the table = 2,045 at significance level 5% which means t count > t table, then Ho rejected Ha accepted. So it can be concluded that there is a significant influence on the use learnig model of tutor coeval.